Regional innovation in the digital economy: an holistic conceptual framework - Valerio Elia (European Regional Science Association (ERSA), 2002)
In this paper we describe a conceptual framework for innovation creation and regional growth in the Digital Economy. The view taken in this paper is that the innovation processes and the spatial organization of economic activities are strongly affected by the new competitive environment, usually defined as Digital Economy, generated by the evolution of the Information and Communication Technologies (ICT) and the related structural adjustments of which the globalization is the most evident. The assumptions on which the conceptual framework is based are: - Innovation and growth can be interpreted in terms of co-evolution of technologies and structures (following an evolutionary approach to the economic change); - Innovation processes strongly depend on the learning and knowledge creation capabilities of the agents of the system; - The Global Economy is characterized by the increasing mobility of firm specific resources and capabilities - especially knowledge-related assets - and by the growing significance of cross border transactions; - The spatial patterns of growth and the unequal distribution of innovation clusters within the same country privilege a regional level of analysis; - The phenomenology about the national innovation systems and the dynamics of the new global environment require the establishment of linkages with the national and global levels. In our conceptual framework growth is related to innovation and innovation in turn is related to learning processes and knowledge creation processes that take place in a region. These processes involve firms but also formal organizations like Universities, local government, etc. other than individuals. What is changing in the new environment is that: - The Digital Economy is accelerating the learning and knowledge creation processes, so that competitiveness increasingly depends on their speed. As for organizations, to manage efficiently these processes we introduce the Intellectual Capital concept also for regions. In the Intellectual Capital framework the dynamic, and hence the evolution, of the system is generated by the mutual interactions among Human, Social, and Structural Capital; - The Global Economy requires a new perspective in the regional-national-global dynamic of the economic system. In terms of policy implications, we propose three linkages that a region should develop to connect its innovation system to the rest of the world and hence to sustain the dynamic of the Intellectual Capital framework. These linkages are:Trade and financial markets linkages that, according to the recent survey of the International Monetary Fund, represent channels for transmitting disturbances internationally. These linkages determine the structure of economic interdependence among the major advanced economies; - Human Capital markets (i.e. to the talents market) linkages. A knowledge-based economy require the access to and the development of skills and competencies; - Global learning system linkages. These linkages, strongly enabled by the ICTs, allow the access to the knowledge universally generated for example from Universities, research centres, etc. but also to the knowledge created from the MNEs through Foreign Direct Investments, strategic alliances, etc.
Keywords: 330